2014
DOI: 10.1108/hff-03-2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

Heat and mass transfer in a porous medium filled rectangular duct with Soret and Dufour effects under inclined magnetic field

Abstract: Purpose -The purpose of this paper is to study the effects of Soret and Dufour effects on convective heat and mass transfer flow through a porous medium in a rectangular duct in the presence of inclined magnetic field. Design/methodology/approach -Using the non-dimensional variables, the governing equations have been transformed into a set of differential equations, which are non-linear and cannot be solved analytically, therefore finite element method has been used for solving the governing equations. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Eliminating the heat flux from the Equations (2) and (3) and introducing the Dufour effect (D 1 ), we get the DPL heat conduction model, which is given in the Equation (5). Using the same analogy, the DPL model for concentration is given in Equation (6). The energy dissipations are ignored.…”
Section: Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Eliminating the heat flux from the Equations (2) and (3) and introducing the Dufour effect (D 1 ), we get the DPL heat conduction model, which is given in the Equation (5). Using the same analogy, the DPL model for concentration is given in Equation (6). The energy dissipations are ignored.…”
Section: Of the Problemmentioning
confidence: 99%
“…2 Moreover, due to the increasing applications of the magnetic field in industrial processes, research on magnetohydrodynamic (MHD) natural convection heat and mass transfer flows in porous media has gained immense interest from scientists and researchers across the globe. Some of the important investigations in this direction are due to Jha, 3 Cheng, 4 Postelnicu, 5 Chamkha et al, 6 Hussanan et al, 7 Seth et al, 8 Seth and Sarkar, 9 Khan et al, 10 Ali et al, 11 Sarkar and Seth, 12 Mohamad et al, 13 Seth et al, 14,15 Bhatti et al, [16][17][18] and Rashidi et al 19,20 In addition, an increasing interest for microchannel fluid mechanics and heat exchange has ascended of late due to plausible cooling applications in space frameworks, material processing, manufacturing activities, and in high power-density chips in supercomputers and different electronics. As this area keeps on developing, it turns out to be progressively essential to comprehend the components and major contrasts required with fluid mechanics and heat transfer in microchannels (Shen 21 ).…”
mentioning
confidence: 99%
“…Mojtabi and Charrier‐Mojtabi confirmed that in liquids the Dufour coefficient is an order of magnitude smaller than the Soret coefficient and concluded that for saturated porous media, the phenomenon of cross diffusion was further complicated because of the interaction between the fluid and the porous matrix and because accurate values of the cross‐diffusion coefficients were not available. Chamkha et al studied heat and mass transfer in a rectangular porous medium duct and examined the Soret and Dufour effects under the inclined magnetic field. Patil and Rudraiah analyzed the general situation, with both cross diffusion and double diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature sheds more light on the various aspects of the Soret effect in cavities [44][45][46][47]. It has been observed that the rate of heat transfer increases with the Soret parameter [48] for a rectangular cavity subjected to an inclined magnetic field. There are various combinations of parameters, such as the magnetic field, inclination angle, and separation parameter that strongly influence heat and mass transfer inside the enclosure [49].…”
Section: Introductionmentioning
confidence: 99%